Draft Seventh Five-Year Plan, 1985-90 and Annual Plan, 1985-86 Volume I Government of West Bengal - Planning Commission (Planning Commission, 1985)
This introductory chapter starts off with a review of performance of the State economy during the Sixth Plan (Section 1). With this review in background,-the strategy for the Seventh Plan, as conceived of at the State level, is then spelt out in general and also separately for the major sectors (Section 2), An important characteristics of this strategy relates t« the organisational set-up for formulation and implementation of the plan schemes. In this context the approach taken in the State towards a decentralised planning organisation has been discussed at the end (Section 3).
Draft Seventh Five-Year Plan, 1985-90 and Annual Plan, 1985-86
Government of West Bengal